Ligand-induced type II interleukin-4 receptor dimers are sustained by rapid re-association within plasma membrane microcompartments - David Richter (Nature Portfolio, 2017)
The contribution of ligands for cytokine receptor dimerization is still not fully understood. Here, the authors show the efficient ligand-induced dimerization of type II interleukin-4 receptor at the plasma membrane and the kinetic trapping of signalling complexes by actin-dependent membrane microdomains.